Religious Violence and Hagiography in Late Antiquity - Marcos, Mar (Numen, 2015)
Sanctity is in many ways a social construct, and hence the profile of saints and the practices that qualify them as such change with the passing of time. The destruction of temples and idols as a way to signal sanctity is a good example of this. The subject came to form part of hagiography in the late fourth century, reached its peak in the Theodosian period, and fell off in the sixth century when Christianization was believed to be complete. Hagiography made iconoclasm one of the most extraordinary expressions of divine power, adding it to the saint’s repertoire of miracles and ascetic virtues. The aim of this article is to study the origins and early development of this motif, which legitimated — and subtly encouraged — the use of violence in the conversion process. It is within apologetic and polemical contexts that the episodes of the violent destruction of late antique paganism have to be assessed.